Prevalence of obesity among elderly residing in an urban area of Belgaum - Chingale, Ashwini; Katti, S. M. (International Journal Of Community Medicine And Public Health, 2019)
Background: The elderly population is the fastest growing age group in the world. This demographic transition has important changes in quality of life in this population, given that longevity may be accompanied by non- communicable diseases, functional reduction, increased dependence, and social isolation, which can bring weight gain in the elderly. Among the elderly there is a loss of the lean body mass and increased body-fat percentage. It is a major risk factor for non-communicable diseases and mortality. The objectives of the present study were to estimate the prevalence of obesity among urban elderly using different measurement methods. Methods: It was cross-sectional study conducted between 1st January to 31st December 2013 in 700 individuals aged 60 years and above. The study participants, permanent residents of Ashok Nagar Urban field practice area, were selected using a simple random technique. Obesity was assessed by using WHO Asia-Pacific Guidelines for body mass index (BMI) and WHO waist circumference (WC) guidelines. Data was analyzed by using percentages and kappa statistics. Results: Prevalence of obesity according to BMI criteria was 38.1% and 43.0% among men and women respectively. Measurement of WC showed that 17.4% of men and 46.8% of women suffered from central obesity. There was slight agreement between obesity criteria and central obesity. Conclusions: The study highlights the problem of obesity in urban elderly. The prevalence of obesity in elderly was slightly higher, with predominance in women. An ageing population together with social, economic and lifestyle changes have led to dramatic increase in obesity.